18F-FDG PET in the Diagnosis and Treatment of Primary Central Nervous System Lymphoma. (17th June 2013) - Kawai, Nobuyuki; Miyake, Keisuke; Yamamoto, Yuka; Nishiyama, Yoshihiro; Tamiya, Takashi
Abstract : This paper summarizes the usefulness and limitation of positron emission tomography (PET) with 18 F-fluorodeoxyglucose ( 18 F-FDG) in the diagnosis and treatment of primary central nervous system lymphoma (PCNSL). The 18 F-FDG uptake in typical PCNSL is about 2.5 times higher than that in the normal gray matter, and the tumor can usually be identified visually. The 18 F-FDG uptake pattern and value provide useful information for differentiating PCNSL from other enhancing malignant brain tumors especially glioblastoma (GB). The 18 F-FDG uptake in typical PCNSL is usually homogenous, and the uptake value is significantly higher than that in GB. However, 18 F-FDG PET often fails to show the presence of tumor in the brain as 18 F-FDG uptake is faint in atypical PCNSL such as disseminated or nonenhancing lesions. 18 F-FDG PET is also useful for evaluating the treatment response at a very early stage after the initial treatment. Pretreatment and posttreatment 18 F-FDG uptake values may have a prognostic value in patients with PCNSL. In conclusion, 18 F-FDG PET is very useful in the diagnosis of typical PCNSL and can differentiate PCNSL from other malignant brain tumors. However, the usefulness of 18 F-FDG PET is limited in the diagnosis of atypical PCNSL.